Virus-specific Ribonucleic Acid Synthesis in KB Cells Infected with Herpes Simplex Virus - Flanagan, John F. (1967)
The production of virus-specific ribonucleic acid (RNA) was investigated in KB cells infected with herpes simplex virus. A fraction of RNA annealable to virus deoxyribonucleic acid (DNA) was found in these cells as early as 3 hr after virus inoculation. Production of this species of RNA increased up to 6 or 7 hr after infection, at which time elaboration of virus messenger RNA (mRNA) declined. At 24 hr after infection, the rate of incorporation of uridine into this RNA was approximately one-half of the rate present at 6 hr after inoculation. Nucleotide analysis of the RNA annealable to virus DNA was compatible with that expected for virus mRNA. Centrifugation showed considerable spread in the size of the virus-induced nucleic acid, the bulk of this RNA sedimenting between 12 and 32S. Incorporation of uridine into cell mRNA, ribosomal precursor RNA, and soluble RNA was suppressed rapidly after infection. As is the case with most other cytocidal viruses investigated to date, virus-induced suppression of cell RNA synthesis appears to be a primary mechanism of cell injury.